2023
DOI: 10.1002/tox.23682
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sepsis‐induced acute kidney injury via thecircITCH‐miR‐579‐3p‐ZEB2axis

Abstract: Circular RNAs (circRNAs) are linked to the regulation of sepsis‐induced acute kidney injury (AKI). However, the function of circITCH in the development of sepsis‐induced AKI is still unclear. The levels of circITCH, miR‐579‐3p and ZEB2 were examined by real‐time PCR and immunoblotting. Then, the roles of circITCH in cell viability, apoptosis, and inflammation in lipopolysaccharide (LPS)‐treated HK‐2 cells were evaluated. The further mechanism was investigated using rescue assays. CircITCH was downregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Various CirRNAs such as Circ_35953, Circ_HIPK3, Circ_0114427, CIRC_0114428, Circ_0001714, circ_0020339, Circ_RASGEF1B, Circ_0114428, circ-FANCA, CircNRIP1, circ0001818, and Circ_0001806 [ 16 , 23 , 25 34 ] have been implicated in LPS-induced renal tubular cell apoptosis. Conversely, others such as CircITCH, CircVMA21, CIRC_0008882, and Circ_0091702 [ 35 38 ] exhibit an opposing role. In our present study, we highlight the antiapoptotic role of mmu_Circ_26986, substantiated by both overexpression and knockdown experiments (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Various CirRNAs such as Circ_35953, Circ_HIPK3, Circ_0114427, CIRC_0114428, Circ_0001714, circ_0020339, Circ_RASGEF1B, Circ_0114428, circ-FANCA, CircNRIP1, circ0001818, and Circ_0001806 [ 16 , 23 , 25 34 ] have been implicated in LPS-induced renal tubular cell apoptosis. Conversely, others such as CircITCH, CircVMA21, CIRC_0008882, and Circ_0091702 [ 35 38 ] exhibit an opposing role. In our present study, we highlight the antiapoptotic role of mmu_Circ_26986, substantiated by both overexpression and knockdown experiments (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, ZEB2 is also involved in the inflammatory response of cells and multiple metabolic processes such as cell formation, growth, differentiation, and apoptosis (47)(48)(49). Recent study confirmed that ZEB3 overexpression relieved LPS-induced HK-2 cell apoptosis and inflammatory cytokine production (50). Ding et al showed that ZEB2 could alleviate LPS-induced HK2 cell inflammation (51).…”
Section: Discussionmentioning
confidence: 99%